(untitled) (Research, Society and Development, 2021)
This study is the result of reflections resulting from the practice of a Pedagogical Intervention Project carried out with students of the 8th year of elementary school of a State College in a town of the State of Paraná. It exposes the contributions and potentialities of a Dynamic Geometry software - GeoGebra - and mathematical concepts existing in the construction of the kite for the teaching of flat geometry topics. The objective was to investigate how the use of GeoGebra software and the making of kites can contribute to the teaching of Flat Geometry topics for 8th grade elementary school students. The use of this pedagogical practice helps in the construction of the aforementioned knowledge, as it places the student in a dynamic position of autonomy, when investigating the properties of the content in question. As theoretical contribution were used studies by Soares (2008), Bona (2009), Ramalho (2013), Pereira (2010), among others. Through this pedagogical activity it was possible to observe the potentialities of mathematics teaching through the GeoGebra software, which expands the methodological possibilities of the teacher. Through a questionnaire applied at the end of the activities, the participants were able to present their impressions about the class. The data obtained showed that the use of kite and the above-mentioned program enrich mathematics classes, help the teaching process and favor the integration between mathematics content and new technologies and students’ daily lives.